Interactive Governance dalam Program Kampung Iklim di Kota Bengkulu - Fitra Aini Ramadhani1; Heru Nurasa; Sawitri Budi Utami (CV. Creative Tugu Pena, 2025)
Climate change is a growing and multidimensional problem that impacts all aspects of human life. The Indonesian government is responding to this through various initiatives, one of which is the Climate Village Program (ProKlim), a national program aimed at encouraging community and other stakeholder participation. This study aims to explore how the principles of interactive governance influence the Climate Village Program (ProKlim) in Bengkulu City. Data were collected through in-depth interviews with informants, participant observation, and examination of program documents. Thematic analysis was conducted using source triangulation to ensure validity. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of the Climate Village Program in Bengkulu City has been running quite optimally. Several work programs have been carried out to implement a number of adaptation actions, including flood and landslide control, food security through local agriculture, and climate-related disease control. Meanwhile, the work program that develops independent climate change mitigation includes community-based waste management (Waste Bank), environmental greening, and energy efficiency. In addition to successfully reducing the dangers associated with the impacts of climate change, this program also involves the community in sustainable and environmentally friendly conservation efforts.